Implementasi Pinjaman Online: Membedah Regulasi Utang dalam Dunia Digital di Indonesia - Hardiati, Neni; Latifah, Ida; F, Fitriani (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This research aims to look at debt and receivable regulations. Debts and Receivables are an agreement in which one party provides a loan (creditor) and the other party has an obligation to pay back the money and interest within a certain period of time. Online loans are financial services to bring together lenders and borrowers to carry out loan and borrowing agreements through an electronic system. Also known as fintech lending, peer to peer lending, online loans and technology-based money lending and borrowing services (lpmubt). This research method uses literature studies and trusted news media documents in the case of online loans. If this online loan is linked to the provisions of Article 1754 of the Civil Code, this online debt and receivable agreement still gives rise to rights and obligations in the form of giving certain goods and returning the goods for the same amount. Then, there are rules contained in POJK regulation no. 77/POJK.01/2016 this regulation is the legal basis for the implementation of information technology-based money lending and borrowing services. This regulation also regulates various aspects, including licensing, governance and supervision of fintech companies. The main aim of this regulation is to ensure that online loan services are carried out transparently and fairly, as well as to protect consumers from detrimental business practices.